STYLISTICS ANALYSIS OF THE POEM “THE DOOR IN THE DARK” BY ROBERT FROST - Mochamad Raka Handayani; Fithriyah Inda Nur Abida (Institut Pendidikan Tapanuli Selatan, 2022)
The goal of stylistics is to not only explain the formal features of texts, but also to demonstrate their functional value in text interpretation; or to demonstrate the relationship between literary text and linguistic effects where these are regarded relevant. The study of stylistics is a branch of linguistics that deals with the qualities and variants of language.The purpose of this research is to examine the stylistic features of Robert Frost's poem “The Door in the Dark”. By looking atthe choice of language at phonetic, morphology, graphitic, and semantics, it is found that Robert Frost's writing, viewpoints, and themes are all connected. The data is analyzed using stylistics devices to achieve the goal. It has beenconcluded that Frostused a philosophy girl. number of stylistic devices including cacophony, alliteration, assonance, tonemodulation, denotation, connotation, metaphor, personification, symbolism, and imagery to highlight the idea oflife.